2016
DOI: 10.1111/acem.12924
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Early Educational Interventions in the Emergency Department to Reduce Incidence or Severity of Postconcussion Syndrome Following a Concussion: A Systematic Review

Abstract: Objectives: Concussions or mild traumatic brain injury are a major public health concern accounting for 85% of all brain injuries. Postconcussion syndrome (PCS) has been found to affect between 15 and 25% of patients with concussion 1 year after the initial injury. The goal of this review is to assess the effectiveness of early educational information or interventions provided in the emergency department on the onset and/or severity of PCS.Methods: A comprehensive literature search strategy involving seven ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…A recent systematic review of early educational interventions in the ED for MTBI concluded there are no clear and consistent interventions or standard management practices that exist for this population. 8 The review included five trials conducted in the ED, none of which were high quality. Significant heterogeneity precluded the authors from pooling the results of the ED interventions, which included educational information sheets, telephone or in-person follow-up, and advice for bed rest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review of early educational interventions in the ED for MTBI concluded there are no clear and consistent interventions or standard management practices that exist for this population. 8 The review included five trials conducted in the ED, none of which were high quality. Significant heterogeneity precluded the authors from pooling the results of the ED interventions, which included educational information sheets, telephone or in-person follow-up, and advice for bed rest.…”
Section: Discussionmentioning
confidence: 99%
“…5 Despite the significant disability associated with PCS, there is paucity in the literature surrounding the prevention of PCS in patients with acute MTBI. 8 Current guidelines recommend a period of "cognitive rest" and stepwise return to usual activities following MTBI. [9][10][11][12][13] Cognitive rest is defined as the avoidance of mental activities that may trigger symptoms, such as watching television, using the computer, listening to music, exercising, reading or talking on the phone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review by Eliyahu, Kirkland, Campbell & Rowe (2016) assessed the effectiveness of early educational interventions in the ED. Five studies were included in this systematic review utilizing the PRISMA methodology guidelines.…”
Section: Discharge Practices In the Emergency Departmentmentioning
confidence: 99%
“…It was found that two of the five studies demonstrated significant improvement in patients' PCS symptoms after receiving early educational interventions. Despite these findings, the researchers determined that there was insufficient high-quality evidence to suggest that early interventions decrease PCS symptoms and the authors made no recommendations (Eliyahu, Kirkland, Campbell, & Rowe, 2016). Research is needed to determine what interventions are best for MTBI patients in order to produce evidence-based guidelines and improve outcomes.…”
Section: Discharge Practices In the Emergency Departmentmentioning
confidence: 99%